2018
DOI: 10.3389/fmicb.2018.02731
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Sediment Microbial Functional Capacity and Community Interaction Networks in an Urbanized Coastal Estuary

Abstract: Coastal estuaries and bays are exposed to both natural and anthropogenic environmental changes, inflicting intensive stress on the microbial communities inhabiting these areas. However, it remains unclear how microbial community diversity and their eco-functions are affected by anthropogenic disturbances rather than natural environmental changes. Here, we explored sediment microbial functional genes dynamics and community interaction networks in Hangzhou Bay (HZB), one of the most severely polluted bays on Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 56 publications
5
16
0
Order By: Relevance
“…The stability difference between upper and lower Bay could be due to the different disturbance and interference from freshwater vs. oceanic water. Similar environmental variations were also found in many other estuaries, and spatial variation also could affect bacterial associations, including Ems estuary [92], Hangzhou Bay [43,53] and Pearl River Estuary [104]. River input, land runoff, suspended particles/turbidity, and accompanied nutrients availability are all pulsating with strong seasonal/inter-annual variations and uncertain patterns in the upper Bay.…”
Section: Seasonal and Spatial Variations Of Cb Microbial Networkmentioning
confidence: 55%
See 1 more Smart Citation
“…The stability difference between upper and lower Bay could be due to the different disturbance and interference from freshwater vs. oceanic water. Similar environmental variations were also found in many other estuaries, and spatial variation also could affect bacterial associations, including Ems estuary [92], Hangzhou Bay [43,53] and Pearl River Estuary [104]. River input, land runoff, suspended particles/turbidity, and accompanied nutrients availability are all pulsating with strong seasonal/inter-annual variations and uncertain patterns in the upper Bay.…”
Section: Seasonal and Spatial Variations Of Cb Microbial Networkmentioning
confidence: 55%
“…Co-occurrence networks can reveal information on associations within microbiomes and stability of whole communities [31,36,37]. It has been increasingly used to infer microbial interactions [30,38] in soils [39,40], oceans [41,42], coastal waters [43], lakes [44,45], rivers [46], and even in metabolic modeling [47] and genomic surveys [48]. These correlation-based networks show important details of community interaction rules re ecting ecological processes such as cooperation and habitat partitioning and could represent mathematical associations among different microbial groups [30,37].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we determined the linear relationship between copies of ARGs ( Supplementary Tables S7 and S8 ) and rrn copy number ( Supplementary Table S9 ) based on the metagenomics data of HB from previous studies ( Figures 7C , D ; Dai et al, 2016 , 2018 ). And the copies of ARGs normalized by prokaryotic cell showed higher correlation ( R 2 = 0.52, p < 0.05) with rrn copy number, indicating that rrn copy number was more likely to represent the intrinsic antibiotic resistance.…”
Section: Resultsmentioning
confidence: 99%
“…On a global scale Zinger et al (2011) observed Bacilli and Clostridia in higher abundances in coastal sediments vs. open water or deep-sea sediments. Bacilli and Clostridia can be indicators of urban fecal contamination in coastal watersheds, lagoons, and nearshore seawater ( Wu et al, 2010 ; Dubinsky et al, 2012 ; Dai et al, 2018 ). As the Beaufort Sea is extremely remote from urban life, it is not surprising that these taxa were less prevalent.…”
Section: Discussionmentioning
confidence: 99%